PERAN BADAN PERWAKILAN RAKYAT DAN BADAN PERADILAN DALAM PEMBERHENTIAN PRESIDEN DAN/ATAU WAKIL PRESIDEN (STUDI PERBANDINGAN DI INDONESIA DAN AMERIKA SERIKAT): The Role of the People's Representative Council and the Judiciary in the Impeachment of the President and/or Vice President (A Comparative Study between Indonesia and the United States) - Chrystyan Nadin Cleviandra Hidayat; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2025)
The manifestation of popular sovereignty in a country necessitates the role of a representative body in the impeachment of the president and/or vice president. However, it is also common for countries to involve judicial institutions in the impeachment process. The research questions in this research are: How do the roles of representative bodies in Indonesia and the United States compare in the impeachment of the president and/or vice president? And how does the involvement of judicial institutions in the impeachment of the president and/or vice president differ between Indonesia and the United States? The research method used is normative legal research, with a descriptive writing approach. Data types include secondary data with primary legal materials, secondary legal materials, and tertiary legal materials, and conclusions are drawn using deductive logic. The findings reveal that the representative bodies in Indonesia and the United States have similarities in initiating the impeachment of the president and/or vice president, and that the decision to impeach is only a removal from office. However, in Indonesia, one chamber, the Regional Representative Council, does not play a role in the impeachment of the president and/or vice president. In contrast, both the House of Representatives and the Senate in the United States have roles in the impeachment process. The comparison of judicial roles shows a clear difference. The Supreme Court of the United States does not play a role in the impeachment process, whereas the Constitutional Court of Indonesia does.